2002
DOI: 10.1053/euhj.2001.2805
|View full text |Cite
|
Sign up to set email alerts
|

Plasma tumour necrosis factor-α and early carotid atherosclerosis in healthy middle-aged men

Abstract: The plasma TNF-alpha concentration is associated with degrees of early atherosclerosis and correlates with metabolic and cellular perturbations that are considered important for the vascular process.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
157
0
6

Year Published

2003
2003
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 242 publications
(169 citation statements)
references
References 30 publications
6
157
0
6
Order By: Relevance
“…In particular when HAECs were incubated with fenofibrate in the presence of oxidized LDL the effect of the medication was reversed (Figure 1 and Figure 4). While it is impossible to replicate the atheromatous environment in vitro, both TNF-α and oxidized LDL have been demonstrated within atherosclerosis and shown to modulate TM expression, supporting the relevance of these studies [31][32][33][34][35]. There are a number of other mechanisms which may account for the inter-sample variation in response to PPAR ligand incubation in this study.…”
Section: Discussionsupporting
confidence: 73%
“…In particular when HAECs were incubated with fenofibrate in the presence of oxidized LDL the effect of the medication was reversed (Figure 1 and Figure 4). While it is impossible to replicate the atheromatous environment in vitro, both TNF-α and oxidized LDL have been demonstrated within atherosclerosis and shown to modulate TM expression, supporting the relevance of these studies [31][32][33][34][35]. There are a number of other mechanisms which may account for the inter-sample variation in response to PPAR ligand incubation in this study.…”
Section: Discussionsupporting
confidence: 73%
“…Resident B cells produce IL-6 and TNF-a. Elevated serum levels of these cytokines are generally found in patients having a poor prognosis or more severe arterial lesions (55,56). Animal models designed to decipher the role of IL-6, TNF-a, and GM-CSF in atherosclerosis have not yet been fully conclusive because experimental settings (feeding diet, location of the lesions, and sex of the animals) largely determine the outcome of lesion evolution (57)(58)(59)(60)(61)(62)(63)(64).…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies in healthy men showed that smoking status had no effect on TNF-a concentrations. 32,34 Macrophage cells secrete more TNF-a in the presence of lower concentrations of smokeless tobacco than in the presence of higher concentrations. 35 Vayssier et al 36 also observed, as we did, that tobacco was related with decreased TNF-a concentrations, and concluded that it could abolish TNF-a cellular release.…”
Section: Discussionmentioning
confidence: 99%